Frequency of Intracranial Hemorrhages in Medico-Legal Death Cases - Naseem Akhter, Fayaz Ahmed Memon, Ambreen Tariq Chattha, Abdul Samad, Aliya Abrar, Aisha Rasheed Shaikh (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To analyze the occurrence of cerebral bleeding in medically assisted deaths. Study Design: Cross-sectional Place of Study: Department of Forensic Medicine & Toxicolgy, Peoples University of Medical & Health Sciences for Women (PUMHSW), SBA and Peoples Medical College Hospital (PMCH) Nawabshah, Sindh, Pakistan from 1st October 2021 to 31st March, 2022. Materials and Methods: For this research, 94 people were enrolled. After obtaining written permission, all of the patient’s demographic information was gathered. Analysis of all patients’ tissue specimens. Toxicology and alcohol testing were performed on the blood sample. All cases were evaluated using X-rays and autopsy were carried out for all of them. Decomposed remains were not included in our research. Results: Among 94 cases, there were 60 (63.8%) males and 30 (36.2%) females. Included patient had mean age 31.45±13.43 years and had mean BMI 22.19±20.48. Frequency of deaths with intracranial lesion was found in 14 (14.9%) cases. We found that frequency of traumatic cases were higher than that of non-traumatic (cerebro-vascular accidents). Frequency of intracranial lesions alone was found in 31 (32.9%) cases. Hemorrhages in the subarachnoid space were the most frequent intracranial pathology. The most prevalent cause of delayed death is pneumonia. Conclusion: The number of deaths that were caused by cerebral trauma was found to be very low in this research; nevertheless, the bulk of deaths were caused by injuries to other anatomical regions.